The accurate temperature measurement method for measurement & verification system of chilled water plant - Ali Asyraf Bin Mohd Haron (2016)
A Heating, Ventilating, and Air-Conditioning (HVAC) Control system operates the mechanical equipment (boilers, chillers, pumps, fans,) to maintain the proper environmental manner. A proper environment is described with four variables: temperature, humidity, pressure and ventilation. Firstly, through component characteristic analysis, hybrid HVAC component models associated with cooling loads, operating variables and energy consumption characteristics for heat exchangers and energy consuming devices are established. All the model parameters can be derived from manufacturers’ specification. The most common HVAC systems that use in large commercial buildings are chilled water systems, and the primary-secondary pumping chilled water loop. In this dissertation, we will only discuss the energy optimization for chilled water systems of large HVAC systems. Firstly, the chilled water systems and the different types of pumping systems. All of these are presented for readers to have a basic concept about the HVAC systems. Then, we present a new approach to optimize the chilled water systems in large HVAC systems for energy optimization.